Моделювання оцінок ризиків надзвичайних ситуацій техногенного та природного характеру - Забулонов, Ю.Л.; Хміль, Г.А. (Моделювання та інформаційні технології, 2009)
In the article mathematical models are represented for determination of estimations of risks of technogenic and natural extraordinary situations.